PHYTOCHEMICAL CONSTITUENTS, PHENOLIC CONTENTS, AND ANTIOXIDANT ACTIVITY OF CRATAEGUS AZAROLUS EXTRACTS - Amina, Boudjada; Ahmed, Touil; Hamdi, Bendif; Chawki, Bensouici; Salah, Rhouati (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Objective: The aim of this study was the isolation and identification of secondary metabolites from Crataegus azarolus (L.) and the antioxidant evaluation of its extracts and compounds. Methods: The air-dried powdered parts of the plant were extracted with 70% methanol and fractionated by chloroform, ethyl acetate, and n-butanol. The n-butanol extract was separated using polyamide SC6 column and silica gel TLC. In addition, a fraction of silica gel column of the CHCl3 extract was analyzed by gas chromatography–mass spectrometer (GC–MS). The total phenolic and total flavonoid contents of CHCl3 and n-butanol extracts were estimated. Furthermore, the antioxidant activities of CHCl3, n-butanol extracts, and two flavonoids were evaluated according to five different methods. Results: Eight compounds were identified in CHCl3 and n-butanol extracts, among them, five volatile compounds identified by GC–MS for the 1st time from the species, as well as three known flavonol glycosides identified by spectral analysis (ultraviolet,1H-nuclear magnetic resonance [NMR], and13C-NMR) and by comparison with literature data. The n-butanol extract showed the higher content of polyphenols (307.33 ± 2.33 mg (gallic acid equivalents)/g extract) and flavonoids (143.0 ± 2.12 mg QE/g extract) and it proves the highest antioxidant activity with all assays used. Conclusion: Five volatile compounds were identified for the 1st time from the C. azarolus and the antioxidant potential of plant extracts was measured using five different methods.